Antiviral Susceptibilities of Distinct Lineages of Influenza C and D Viruses - Takashita, Emi; Murakami, Shin; Matsuzaki, Yoko; Fujisaki, Seiichiro; Morita, Hiroko; Nagata, Shiho; Katayama, Misa; Mizuta, Katsumi; Nishimura, Hidekazu; Watanabe, Shinji; Horimoto, Taisuke; Hasegawa, Hideki (Viruses, 2023)
The emergence and spread of antiviral-resistant influenza viruses are of great concern. To minimize the public health risk, it is important to monitor antiviral susceptibilities of influenza viruses. Analyses of the antiviral susceptibilities of influenza A and B viruses have been conducted globally; however, those of influenza C and D viruses are limited. Here, we determined the susceptibilities of influenza C viruses representing all six lineages (C/Taylor, C/Yamagata, C/Sao Paulo, C/Aichi, C/Kanagawa, and C/Mississippi) and influenza D viruses representing four lineages (D/OK, D/660, D/Yama2016, and D/Yama2019) to RNA polymerase inhibitors (baloxavir and favipiravir) by using a focus reduction assay. All viruses tested were susceptible to both drugs. We then performed a genetic analysis to check for amino acid substitutions associated with baloxavir and favipiravir resistance and found that none of the viruses tested possessed these substitutions. Use of the focus reduction assay with the genotypic assay has proven valuable for monitoring the antiviral susceptibilities of influenza C and D viruses as well as influenza A and B viruses. Antiviral susceptibility monitoring of all influenza virus types should continue in order to assess the public health risks posed by these viruses.